2013
DOI: 10.1185/03007995.2013.855188
|View full text |Cite
|
Sign up to set email alerts
|

Early and sustained improvement with vilazodone in adult patients with major depressive disorder: post hoc analyses of two phase III trials

Abstract: Early and sustained improvement of depressive symptoms was retrospectively observed in patients treated with vilazodone; early findings may be related to overall treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Significant differences from placebo occurred at week 1 and week 6 in the two Phase III trials. In the pooled data, a statistically significant difference from placebo occurred with vilazodone at week 1 on MADRS total score and on 7 of 10 MADRS single items at week 1 or 2 [75]. It should be noted that the Phase III studies used a titration design, meaning that subtherapeutic doses of 10 mg were used at week 1.…”
Section: Onset Of Actionmentioning
confidence: 94%
“…Significant differences from placebo occurred at week 1 and week 6 in the two Phase III trials. In the pooled data, a statistically significant difference from placebo occurred with vilazodone at week 1 on MADRS total score and on 7 of 10 MADRS single items at week 1 or 2 [75]. It should be noted that the Phase III studies used a titration design, meaning that subtherapeutic doses of 10 mg were used at week 1.…”
Section: Onset Of Actionmentioning
confidence: 94%
“…In this category, vilazodone, a 5-HT1A receptor partial agonist and SSRI [86][87][88], offers a new therapeutic possibility [89,90]. It has been shown that vilazodone induces an elevation of 5-HT amounts in the medial and the lateral cortex that is six-fold higher than those induced by SSRIs paroxetine, citalopram or fluoxetine [86].…”
Section: Effects Of Novel Strategiesmentioning
confidence: 99%
“… 12 Because of its unique action mechanism, indirect evidence enabled clinicians to speculate that vilazodone may potentially provide faster treatment onset along with enhanced remission and response rates with lower AE risks than preexisting anti-depressants. 13 , 14 , 15 Preclinical studies and indirect evidences did suggest that vilazodone might result in faster treatment onset than conventional selective serotonin reuptake inhibitors (SSRIs), 16 , 17 but no direct comparative trials confirmed vilazodone's superiority over other antidepressants.…”
Section: Introductionmentioning
confidence: 99%